Hospitalization rates among patients with cystic fibrosis using pancreatic enzyme replacement therapy. (23rd January 2020) - Trapnell, Bruce C.; Chen, Su; Khurmi, Rupal; Bodhani, Amit; Kapoor, Mudra; Haupt, Mark
We investigated the relationship between self-reported adherence to pancreatic enzyme replacement therapy (PERT), nutritional status, and all-cause hospitalization in cystic fibrosis (CF) patients with a record of PERT use. Association of self-reported annual PERT use rate (adherence) with annual hospital admission rate (HAR) and annual total hospital nights (THNs) were analyzed for 5301 children (2000–2012) and 13, 989 adults (2000–2013) from the CF Foundation Patient Registry. Multivariate linear regression was used to determine the association of HAR and THN with mean annual PERT use rate, cumulative PERT use rate, mean body mass index (BMI) (adult) or BMI percentile (pediatric), age, and sex. The median annual PERT use rate was 87% in children and 80% in adults. Statistically, higher annual PERT use, longer cumulative PERT, and higher BMI percentile (children) or BMI (adults) were significantly ( p < 0.0001) associated with lower annual HAR and fewer annual THN in children and adults. Female sex was associated with higher annual HAR and more annual THN in children and adults ( p < 0.05). Results indicate self-reported adherence to PERT, increased BMI, and male sex were associated with fewer hospital admissions and annual hospital nights in CF patients.